2014
DOI: 10.1111/ijn.12318
|View full text |Cite
|
Sign up to set email alerts
|

Profiling nurses' job satisfaction, acculturation, work environment, stress, cultural values and coping abilities: A cluster analysis

Abstract: This study aimed to determine whether definable profiles existed in a cohort of nursing staff with regard to demographic characteristics, job satisfaction, acculturation, work environment, stress, cultural values and coping abilities. A survey was conducted in one hospital in Singapore from June to July 2012, and 814 full-time staff nurses completed a self-report questionnaire (89% response rate). Demographic characteristics, job satisfaction, acculturation, work environment, perceived stress, cultural values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
0
25
1
4
Order By: Relevance
“…Jednym z nich jest niski poziom satysfakcji zawodowej. Na podstawie przeprowadzonych badań stwierdza się, że powodem odchodzenia z zawodu jest brak satysfakcji, na który składają się konkretne czynniki [6].…”
Section: Wprowadzenieunclassified
“…Jednym z nich jest niski poziom satysfakcji zawodowej. Na podstawie przeprowadzonych badań stwierdza się, że powodem odchodzenia z zawodu jest brak satysfakcji, na który składają się konkretne czynniki [6].…”
Section: Wprowadzenieunclassified
“…For new graduates, job stress correlated negatively with job satisfaction, but in those who stayed job satisfaction increased significantly beyond the first year . Goh et al . found that younger nurses reported higher intention to leave, stress and job dissatisfaction, and felt this group should be prioritiszed.…”
Section: Gen Y Vs the Boomers?mentioning
confidence: 99%
“…For new graduates, job stress correlated negatively with job satisfaction, but in those who stayed job satisfaction increased significantly beyond the first year. 5 Goh et al 6 found that younger nurses reported higher intention to leave, stress and job dissatisfaction, and felt this group should be prioritiszed. By contrast, the value of older workers was flagged, with Jiang et al 7 reporting development of competency with increasing age, and proposed that accumulation of a rich life and work experience and better competency might promote caring behaviours in nurses.…”
Section: Gen Y Vs the Boomers?mentioning
confidence: 99%
“…We should treat nurses and midwives in their workplace to the same consideration for their health and wellbeing that we accord their patients. We recognise the individuality of patients; we should do the same for staff and, at the least, recognise the differing needs of younger and older nurses . To date we seldom target nurses and midwives for health promotion .…”
mentioning
confidence: 99%
“…We recognise the individuality of patients; we should do the same for staff and, at the least, recognise the differing needs of younger and older nurses. 2,3 To date we seldom target nurses and midwives for health promotion. 4 Rectifying this, we should look for ways to make it easy to exercise, eat well, stop smoking and develop resilience and healthy coping strategies; incorporate health education and routine screening within the working day.…”
mentioning
confidence: 99%